Online Learning During COVID-19 Pandemic: A Response to Challenges in Instructional Emergency - Tamah, Siti; Teopilus, Susana (Celt: A Journal of Culture, English Language Teaching & Literature, 2022)
Many studies highlight online instructional issues in an ordinary situation; however, this article is oriented to a very restricted online course in an extraordinary condition – the COVID-19 pandemic realm. The objectives of this article are (1) to portray how Writing-A lecturers within such a short time preparation conducted the online courses to achieve the course objectives, and (2) to depict how Writing-A students perceived the implementation of this online course. The study is based on a half-semester small-scale study project employing institution documents and surveys. The subjects were 43 students in an institution in Indonesia. The results demonstrate the Teaching Presence which was the new challenge faced by the lecturers and the Cognitive and Social presence which occurred in the students’ new online learning. The significance of this study is the disclosure of how the encouragement of communities might contribute to conducive learning for both e-lecturers and e-students.